The interplay of verbs and argument structure constructions in second language processing: roles of verb’s lexical properties and verb–construction association - Kim Hyunwoo; Shin Gyu-Ho (Cognitive Linguistics)
While verbs and argument structure constructions are essential for deriving sentence meaning, their roles in sentence processing remains less known. To address this issue, the present study explored how a verb’s lexical properties and the strength of verb–construction associations influence second language (L2) sentence processing. In two self-paced reading experiments, Korean-speaking learners of English and native English speakers read English argument structure constructions containing verbs with varying lexical properties and association strength. In both Experiment 1 (involving the prepositional dative construction) and Experiment 2 (involving the caused-motion construction), only the L2-English learners, and not the native speakers, spent more time integrating the target constructions with verbs of weaker associations than those with stronger associations. Furthermore, the learners exhibited greater difficulty with verb–construction integration when the verbs were less frequent and less concrete; L2 proficiency did not modulate these effects. Our findings support the constructionist approach, suggesting that both verbs and verb–construction associations play an instrumental role in sentence comprehension.